Higher uric acid serum levels are associated with sarcopenia among elderly in a community health center - A. Deza Farista; Nur Rivianti; Erial Bahar; Mega Permata; Muhammad Reagan; Crisnah Indah; Ika Artini (Universa Medicina, 2025)
BackgroundAs people age, skeletal muscle mass and strength decrease, leading to sarcopenia, diagnosed through calf circumference, muscle mass, strength, and physical performance. Uric acid (UA), with both pro-oxidant and antioxidant properties, is an indicator of oxidative stress and may contribute to sarcopenia. This study aimed to determine the correlation between serum uric acid levels and sarcopenia in elderly in a community health center. MethodsA cross-sectional study was conducted involving 42 subjects aged ≥60 years, consisting of 37 female and 5 male participants. We applied Asian Working Group for Sarcopenia (AWGS) 2019 criteria to define sarcopenia. Muscle mass was measured using skeletal muscle index (SMI) based on bioimpedance analysis (BIA). Handgrip strength (HGS), physical performance, calf circumference, and blood test data were collected. A backward regression analysis was performed to investigate the relationship between UA and SMI, HGS, physical performance, and calf circumference after adjusting for gender, smoking history, upper arm circumference, and body mass index.Results After adjusting for potential confounding variables, uric acid remained significantly associated with muscle strength (β=0.326; p=0.023) and calf circumference (β=0.264; p=0.010), but not with muscle mass (β=0.046; p=0.727) or physical performance (β=–0.171; p=0.279).ConclusionThere is a significant correlation between uric acid levels and muscle strength, physical performance, and calf circumference in sarcopenia among the elderly in the community health center. Higher uric acid serum levels might slow down the progression of sarcopenia.